A Potential Study of HUA–IT Market Aiming as a Collection and Distribution Center of Agricultural Products in Southern of Thailand - Suthummanon, Sakesun; Penjamras, Pallapat; Jaroenjiratrakul, Somboon; Suddsa-oad, Sopin; Sirivongpaisal, Nikorn (IntechOpen, 2012)
None